Application of the component method to traditional dovetail joints of timber trusses - Sobra, Karel (2014)
Timber structures, especially trusses, represent one of the most important ancient engineering structures. But during the lifetime cycle, wood and all members of truss degrade and they need to be repaired. Collar beam truss is one of the most common types of historical trusses in Czech Republic. The most representative joint of this type of timber system is the dovetail joint. It is important to assess the joint behaviour, both in terms of strength and stiffness, not only for the design of new trusses, but specially, for the intervention on existing structures. Unfortunately, during the ages those joints have been constructed by routine and no recommendation for their design exists. The behaviour of this carpentry joint can be analysed through the component method based on the use of springs simulating the strength and stiffness of each component. In this paper the application of this method to dovetail joints is presented and discussed. For that, the behaviour of the dovetail joints have been characterized in terms of geometry, materials, stresses involved and common damages.